New Frontiers in Applied Data Mining PAKDD 2008 International Workshops, Osaka, Japan, May 20-23, 2008. Revised Selected Papers - Chawla, Sanjay; Washio, Takashi; Minato, Shin-ichi.; Tsumoto, Shusaku; Onoda, Takashi; Yamada, Seiji; Inokuchi, Akihiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the proceedings of the PAKDD Workshops 2008, namely ALSIP 2008, DMDRM 2008, and IDM 2008. The workshops were held in conjunction with the PAKDD conference in Osaka, Japan, during May 20-23, 2008. The 17 papers presented were carefully reviewed and selected from 38 submissions. The International Workshop on Algorithms for Large-Sale Information Processing in Knowledge Discovery (ALSIP) focused on exchanging fresh ideas on large-scale data processing in the problems of data mining, clustering, machine learning, statistical analysis, and other computational aspects of knowledge discovery problems. The Workshop on Data Mining for Decision Making and Risk Management (DMDRM) covered data mining and machine learning approaches, statistical approaches, chance discovery, active mining and application of these techniques to medicine, marketing, security, decision support in business, social activities, human relationships, chemistry and sensor data. The Workshop on Interactive Data Mining Overview (IDM) discussed various interactive data mining researches such as interactive information retrieval, information gathering sysetms, personalization systems, recommendation systems, user interfaces.
Workshop of ALSIP 2008 -- Flexible Framework for Time-Series Pattern Matching over Multi-dimension Data Stream -- An Adaptive Algorithm for Splitting Large Sets of Strings and Its Application to Efficient External Sorting -- Incrementally Mining Recently Repeating Patterns over Data Streams -- A Graph-Based Approach for Sentiment Sentence Extraction -- Fuzzy Weighted Association Rule Mining with Weighted Support and Confidence Framework -- A Framework for Mining Fuzzy Association Rules from Composite Items -- Mining Mutually Dependent Ordered Subtrees in Tree Databases -- A Tree Distance Function Based on Multi-sets -- Sibling Distance for Rooted Labeled Trees -- Kernel Functions Based on Derivation -- Workshop of DMDRM 2008 -- Dynamic Bayesian Networks for Acquisition Pattern Analysis: A Financial-Services Cross-Sell Application -- An Automata Based Authorship Identification System -- Detection of Risk Factors as Temporal Data Mining -- Workshop of IDM 2008 -- Two-Phased Active Support Kernel Machine Learning -- Extracting Topic Maps from Web Pages -- Interactive Abnormal Condition Sign Discovery for Hydroelectric Power Plants -- Interactive Visualization System for Decision Making Support in Online Shopping -- A Method to Recognize and Count Leaves on the Surface of a River Using User$1 (Bs Knowledge about Color of Leaves.s
Keywords: Life sciences; Data mining; Information storage and retrieval; Multimedia information systems; User interfaces (Computer systems).; Artificial intelligence; Life Sciences; Life Sciences, general; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Information Storage and Retrieval; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Electronic books